Current Trends, Controversies, and Future Directions in the Evaluation and Management of Superior Canal Dehiscence Syndrome - Eberhard, Kristine Elisabeth; Chari, Divya A.; Nakajima, Hideko Heidi; Klokker, Mads; Cayé-Thomasen, Per; Lee, Daniel J. (Frontiers in Neurology, 2021)
Patients with superior canal dehiscence syndrome (SCDS) can present with a range of auditory and/or vestibular signs and symptoms that are associated with a bony defect of the superior semicircular canal (SSC). Over the past two decades, advances in diagnostic techniques have raised awareness of SCDS and treatment approaches have been refined to improve patient outcomes. However, a number of challenges remain. First, there is currently no standardized clinical testing algorithm for quantifying the effects of superior canal dehiscence (SCD). SCDS mimics a number of common otologic disorders and established metrics such as supranormal bone conduction thresholds and vestibular evoked myogenic potential (VEMP) measurements; although useful in certain cases, have diagnostic limitations. Second, while high-resolution computed tomography (CT) is the gold standard for the detection of SCD, a bony defect does not always result in signs and symptoms. Third, even when SCD repair is indicated, there is a lack of consensus about nomenclature to describe the SCD, ideal surgical approach, specific repair techniques, and type of materials used. Finally, there is no established algorithm in evaluation of SCDS patients who fail primary repair and may be candidates for revision surgery. Herein, we will discuss both contemporary and emerging diagnostic approaches for patients with SCDS and highlight challenges and controversies in the management of this unique patient cohort.